Solvent-free, visible-light photocatalytic alcohol oxidations applying an organic photocatalyst - Obst, Martin; König, Burkhard (Beilstein Journal of Organic Chemistry, 2016)
A method for the solvent-free photocatalytic conversion of solid and liquid substrates was developed, using a novel rod mill apparatus. In this setup, thin liquid films are realized which is crucial for an effective photocatalytic conversion due to the low penetration depth of light in heterogeneous systems. Several benzylic alcohols were oxidized with riboflavin tetraacetate as photocatalyst under blue light irradiation of the reaction mixture. The corresponding carbonyl compounds were obtained in moderate to good yields.
Keywords: benzylic alcohol; oxidation; photocatalysis; solvent free; visible light